MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI AKTIVITAS SENI MUSIK TERHADAP ANAK KELOMPOK B DI TK. ADINDA CAHAYA CIMAHI - Waraswati, Nurpuri; Andriani, Rini (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2018)
Early Childhood Education (PAUD) implements education that refers to all the basic aspects or abilities that are developing in the child. The basic ability of children is very interesting to be studied, one of them cognitive abilities of children. It is raised in connection with the lack of cognitive abilities in Adinda Cahaya kindergarten with the present method mainly through the activity of the art of music. The existing formulation in this study is "The activity of music art that can improve the cognitive abilities of children". The purpose of this study is to describe the cognitive abilities of children in music art activities.. There are six levels of cognitive ability: knowledge, understanding, application of analysis, synthesis and evaluation. Research questions are 1). How does music activity and music learning time to support the development of children's cognitive abilities? 2. How does the child's memory of what the teacher has taught in music art activities? 3) How are children's development related to cognitive ability? The conclusion is that the study of music art gives a positive and influential effect on the child's cognitive development that will stimulate brain development and emotional intelligence.